HMOX1 as a potential drug target for upper and lower airway diseases: insights from multi-omics analysis - Enhao Wang; Shazhou Li; Yang Li; Tao Zhou (Respiratory Research)
Abstract Background Oxidative stress is key in inflammatory airway diseases. Heme oxygenase 1 (HMOX1) regulates oxidative stress, but its role in airway diseases needs exploration. Methods Differentially expressed genes (DEGs) between healthy nasal mucosa and chronic rhinosinusitis with nasal polyps (CRSwNP) were identified from Gene Expression Omnibus (GEO). Candidate genes were further screened using Gene Set Enrichment Analysis (GSEA) and Random Forest (RF) algorithms. Causal inference between candidate genes and upper and lower airway diseases (CRSwNP, allergic rhinitis (AR), and asthma (AS)) was conducted using bidirectional two-sample Mendelian randomization (TwoSampleMR) analysis. Single-cell RNA sequencing (scRNA-seq) data were used to determine the cellular localization and intercellular interactions of candidate genes. Molecular docking was used to identify potential therapeutic agents. Results HMOX1 expression was significantly elevated in CRSwNP. TwoSampleMR analysis indicated a negative causal relationship between HMOX1 exposure and the occurrence of upper and lower airway diseases (CRSwNP [(odds ratio (OR)/95% confidence interval (CI): 0.945/(0.893–0.999), P = 0.044], AR [OR/95% CI: 0.997/(0.994–0.999), P = 0.007], and AS [OR/95% CI: 0.935/(0.895–0.977), P = 0.003]). scRNA-seq data revealed HMOX1 localization in M2 macrophages. Molecular docking identified 15 antioxidants, including Acetylcysteine and Quercetin, that can upregulate HMOX1 expression. Conclusion HMOX1 may have a protective role in the pathogenesis of upper and lower airway diseases (CRSwNP, AR, and AS) by modulating oxidative stress. Antioxidants that increase HMOX1 expression could offer new therapeutic avenues for these diseases. Clinical trial Not applicable.